Mass Incarceration in California Counties: A Mechanism for Educational Inequality. Issue 2 (3rd April 2017) - Aylward, Alexandra
Abstract: Although there is substantial evidence of the negative effects of being incarcerated or having a father imprisoned, there is little research on the spillover effects created by the concentration of incarceration within disadvantaged communities. This article addresses this limitation by investigating the association between mass incarceration and the educational outcomes of all Black and White children living in a community where many of its members were incarcerated across counties within California from 2009 to 2013.